2021
DOI: 10.3389/fmolb.2021.679797
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Plasticity and Atherosclerosis Therapy

Abstract: Atherosclerosis is a chronic disease starting with the entry of monocytes into the subendothelium and the subsequent differentiation into macrophages. Macrophages are the major immune cells in atherosclerotic plaques and are involved in the dynamic progression of atherosclerotic plaques. The biological properties of atherosclerotic plaque macrophages determine lesion size, composition, and stability. The heterogenicity and plasticity of atherosclerotic macrophages have been a hotspot in recent years. Studies d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 257 publications
(365 reference statements)
3
89
1
1
Order By: Relevance
“…The major finding in this work is that inhibition of atherosclerosis by a selective FFAR4 agonist TUG-891 is associated with a significant shift in the polarization of macrophages in atherosclerotic plaques towards the M2 phenotype. It has been demonstrated that macrophages in plaques are highly pleiotropic and retain the capacity to shift their polarization [ 16 ]. Our data point to the role of FFAR4 in the modulation of macrophage phenotype and, in a more general context, also highlight the importance of in-plaque balance between different macrophage phenotype species as an important modulator of atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The major finding in this work is that inhibition of atherosclerosis by a selective FFAR4 agonist TUG-891 is associated with a significant shift in the polarization of macrophages in atherosclerotic plaques towards the M2 phenotype. It has been demonstrated that macrophages in plaques are highly pleiotropic and retain the capacity to shift their polarization [ 16 ]. Our data point to the role of FFAR4 in the modulation of macrophage phenotype and, in a more general context, also highlight the importance of in-plaque balance between different macrophage phenotype species as an important modulator of atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…M2 represents an atypical, activated monocyte that produces a significant amount of monocyte-colony stimulating factor (M-CSF) and free radicals, while not being able to mount an effective response to invading pathogens. These cells are frequently implicated in the emergence of atherosclerosis and immunosuppression [ 185 ]. Ingestion of apoptotic cells, commonplace in sepsis, and abnormal cholesterol metabolism is often linked to their emergence [ 186 , 187 ].…”
Section: Lipid Metabolism During Acute Sepsismentioning
confidence: 99%
“…Mox macrophages (proatherogenic subset) are triggered by modified phospholipids and defend against oxidative stress utilizing a 2-nuclear factor-related factor 2 linked with erythroid, mediated by the expression of the antioxidant enzymes such as heme oxygenase 1, thioredoxin reductase 1, and sulfiredoxin–1 [ 51 , 52 ]. It is reported that in mice with hypercholesterolemia, Mox macrophages make up 30% of plaque macrophages, with subsets M1 equals 40% and M2 equals 20% of the remaining cohort, accordingly [ 53 ]. Ultimately, M4 macrophages are a subset polarized by platelet factor 4.…”
Section: Macrophages In Atherosclerosismentioning
confidence: 99%
“…Although the foam cells obtained from SMC acquire macrophage markers (for example, CD68 and Lgals3), as well as storing cholesterol and lipoproteins, they do not acquire phagocytic or efferocytic abilities and, accordingly, do not turn into real macrophages [ 53 ]. However, the simultaneous loss of SMC markers complicates the separation of foam cells obtained from SMS from their analogues obtained from monocytes.…”
Section: Foam Cells Are Not Always Macrophage-derivedmentioning
confidence: 99%